The System for Statistical Measurement of Digital Economy Parameters: Development Trends - Аrtemieva І. О. (Statistics of Ukraine, 2020)
The main challenges faced by statistical activities under the pressure of the global dissemination of digital technologies are outlined. The need for constructing a comprehensive system for measurement of digital economy parameters is demonstrated, and the requirements with which it has to comply are set. The principal trends of the process involved in the development of the system for measurement of digital economy parameters are determined. The need for elaboration, implementation and formalization of the metadata laying the ground for constructing the system for statistical measurement of digital transformations, and for making the relevant regulatory base is substantiated; the difficulties involved in this process are outlined. A comparative description of the views held by proponents and opponents of change in the traditional conceptual framework for measurement of economic parameters in the new conditions is given. Problems are highlighted that are associated with constructing a new model of statistics for the digital economy, supposed to integrate all the existing methodical and methodological elaborations in the field of information society’s statistics, on the one hand, and offer new approaches to statistical measurement of various aspects of digitalization, on the other. Main problems related with creating an appropriate information base for constructing the indicators that would report on digital economy components are determined, with outlining ways for their solution. The essential types of efforts on modernization of technological facilities in the official statistics system are shown. Change in the pattern of the demand for statistical information is described, and ways to improve feedback of statistical information users are proposed. It is justified that the staff of statistical offices needs to build the competencies required for design of digital technologies and their use in the professional activities; recommendations on the content of training and professional development programs are given. It is demonstrated that practices of digital economy measurement and dissemination of its results need to be globally standardized; the role of international organizations in optimization and standardization of various processes involved in the production of official statistics at national and international level is highlighted. Potential areas of future efforts in constructing the system for measurement of digital economy are outlined.